Leadership Skills Development for Educational Leadership to Improve Organizational Effectiveness in Higher Education - Kaewumpai, Wallapat (Scholar: Human Sciences, 2015)
Thai higher education is facing difficulties and challenges to perform effectively. Leadership skills among university leaders are a barrier to improve the organizational effectiveness. This research was guided by theoretical frameworks that were most relevant to leadership skills and organizational effectiveness. This research focused on finding the most appropriate leadership skills for top executives in higher education institutions that affect the organization effectiveness by using Public Sector Management Award (PMQA) as an assessment model. The results showed 10 leadership skills that affect the organizational effectiveness including: inspiring the shared vision; challenging staff in establishing a set of goals to implement the shared vision; crafting the initiative with staff to achieve goals; enabling staff to implement the plan; providing budget and allocating resources to support the plan; coaching (encouraging the heart) the leadership teams; modeling key processes to manage change and solve problems; constructing collaborative network (facilitating) among all stakeholders; maintaining performance expectations; and recognizing and rewarding staff.